SCE554 : Problem solving in science / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
The course is designed to introduce students to the concepts and theory related to problem solving in science. Students will explore and evaluate scientific issues and propose suitable solution for the problems. The problems vary and related to Physic, Chemistry, Biology and other science-based problems. The SSCS model for problem solving will be applied and discussed in detail. The emphasis is on exploration of various science contexts, to pose problems and problem extensions, to solve problems and to communicate and share with others. Constructivist learning will be emphasized in the problem solving in science.